The Purkinje network plays a major role in low-energy ventricular defibrillation. (February 2022) - Bayer, Jason D.; Sobota, Vladimír; Moreno, Angel; Jaïs, Pierre; Vigmond, Edward J.
Abstract: Background: During ventricular fibrillation (VF), targeting the excitable gap (EG) of reentry throughout the myocardium with low-energy surface stimulation shows promise for painless defibrillation. However, the Purkinje network may provide alternative pathways for reentry to evade termination. This study investigates the role of the Purkinje network in painless defibrillation. Methods: In a computational human biventricular model featuring a Purkinje network, VF was initiated with 4 Hz epicardial pacing. Defibrillation was attempted by stimulating myocardial surface EG with a low-energy 2 ms duration pulse at 2x stimulus capture, which was administered at coupling intervals incremented by 0.25 s between 0.25 and 5 s after VF initiation. Defibrillation was accomplished if reentry ceased ≤ 1 s after the defibrillation pulse. The protocol was repeated with the Purkinje network and myocardial surface EG stimulated simultaneously, and again after uncoupling the Purkinje network from the myocardium. Results: VF with the Purkinje network coupled and uncoupled had comparable dominant frequency in the left (3.81 ± 0.44 versus 3.77 ± 0.53 Hz) and right (3.80 ± 0.37 versus 3.76 ± 0.48 Hz) ventricles. When uncoupling the Purkinje network, myocardial surface EG stimulation terminated VF for all defibrillation pulses. When coupled, myocardial EG surface stimulation terminated VF for only 55 % of the defibrillation pulses, but improved to 100 % when stimulated simultaneously with Purkinje network EG. Defibrillation failures were attributed to EG evading stimulation in the Purkinje network. Conclusions: Defibrillation that exclusively targets myocardium can fail due to accessory pathways in the Purkinje network that allow for reentrant activity to evade termination and maintain VF. Painless defibrillation strategies should be adapted to include the Purkinje network. Highlights: A state-of-the-art approach was deployed to investigate defibrillation outcome in response to low-energy surface stimulation. Defibrillation with low-energy surface stimulation fails when reentrant activity evades termination in the Purkinje network. Stimulating the Purkinje network or uncoupling the Purkinje network from the myocardium increased defibrillation efficacy. Disabling the Purkinje network can increase the efficacy of cardiac electrotherapies that target the ventricular myocardium.